Learning physics at science centers: Use of visitors’ drawings to investigate learning at an interactive sound exhibit - McClafferty, T.; Rennie, Leonie (2017)
© 2017 Sense Publishers. All Rights Reserved. Science centers and museums use interactive exhibits to teach visitors about scientific concepts. Feher (1990) referred to such exhibits as “powerful learning tools”, and stated that “for the user they constitute an independent, teacher-free, learning device; and for the researcher they are the means for rendering explicit user’s conceptions and studying the learning process” (p. 46). It is important for the center and museum managers, and the exhibit designers, to understand the exhibit’s effectiveness.